Contribution to the karyomorphology of some species of the genus Quercus - D'Emerico, S.; Paciolla, C.; Tommasi, F. (SILVAE GENETICA, 2000)
In order to contribute to the knowledge of the taxonomic relationships between some species of the Quercus genus, the karyomorphology of 4 species (Quercus ilex L., Q, suber L., Q. robur L, and Q. pubescens WILLD.) was carried out. The somatic chromosome number 2n=24 was found in all taxa examined. An evident differentiation in karyotype structure of Q. ilex compared to other previous studied species has been found. Quercus suber, Q. robur and Q. pubescens possess moderately asymmetrical karyotypes. Q. suber differs from other species of the subgenus Cerris on the basis of karyological data showing similarities with Q, robur and Q. pubescens.
The following values have no corresponding Zotero field: pub-location: FINKENHOFSTRASSE 21, W-6000 FRANKFURT, GERMANY publisher: SAUERLANDERS VERLAG
Keywords: B. pubescens; karyotype; Q. robur; Q. suber; Quercus ilex